HPLC analysis, genotoxic and antioxidant potential of Achillea millefolium L. and Chaerophyllum villosum Wall ex. Dc - Muhammad Adil; Ghulam Dastagir; Atifa Quddoos; Muhammad Naseer; Faten Zubair Filimban (BMC, 2024)
Abstract Background Methanolic and chloroformic extract of Achillea millefolium and Chaerophyllum villosum were evaluated for HPLC analysis, genotoxic and antioxidant potential. Materials and methods Genotoxic activity was carried out on human blood lymphocytes via comet assay and antioxidant activity was studied through DPPH method. Results The genotoxic potential of A. millefolium and C. villosum's methanolic and chloroformic extract was analysed using comet assay technique. Comet shaped human lymphocytes cells were observed when treated with different concentrations (50 mg/mL, 75 mg/mL, 100 mg/mL) of methanolic and chloroformic extract of both plants. Reading was taken on the basis of damaged DNA head and tail length. Greater the length of tail as compared to head, greater will be the damage and vice versa. Total comet score was obtained from A. millefolium subjected to different concentrations. After a time interval of 24 h both the extract showed dose dependant genoprotection with maximum genoprotectivity at 98.7 ± 12.7 and 116 ± 5.3 at 50 mg/100 mL for methanolic and chloroformic extract respectively. Similarly Total Comet score was obtained from C. villosum subjected to different concentrations of methanolic and chloroformic extract. After 24 h exhibited dose dependent genoprotection with maximum protectivity at 85.7 ± 22.0 and 101.7 ± 8.6 at 50 mg/100 mL for methanolic and chloroformic extract were determined. The antioxidant activity revealed that methanolic extract of A. millefolium showed highest antioxidant activity (84.21%) at 300 mg/ml after 90 min while the chloroformic extract of C. villosum exhibited highest (68.46%) antioxidant activity (59.69%) at 300 µg/ml after 90 min but less than the standard drug ascorbic acid (88.72%). Quantitative phytochemical screening revealed high percentage of alkaloids (27.4%), Phenols (34.5%), Flavonoids (32.4%) as compared to Tannins (12%) in methanolic extract of A.millefolium. While high percentage of alkaloids (31.4), Phenols (19.3%), Flavonoids (35.5%) as compared to Tannins (16.6%) in chloroformic extract of C. villosum. Conclusion The present results showed that A. millefolium and C. villosum possess a number of important compounds and revealed genoprotective property which may be used to treat several genetic disorders such as alzeimer's disease in future (Grodzicki W, Dziendzikowska K, Antioxidants 9(3):229, 2020).